2007
DOI: 10.1002/hyp.6314
|View full text |Cite
|
Sign up to set email alerts
|

Xylem sap flows of irrigated Tamarix elongata Ledeb and the influence of environmental factors in the desert region of Northwest China

Abstract: Abstract:Tamarix elongata Ledeb is a desert shrub found in the desert region of Northwest China and is commonly cultivated as a sand-holding plant in this region. To understand its water requirement and the effects of climate conditions on its growth, trunk xylem sap flows of irrigated 8-year-old Tamarix elongata Ledeb plants were monitored continuously with heat-pulse sap flow meters for the entire season. Soil moisture contents at 0-300 cm layer depth were also measured with a tube type time domain reflectom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 20 publications
(27 reference statements)
4
24
0
Order By: Relevance
“…Sap flow measurements have been widely used to study plant response to environment factors (Cermak et al, 2004;Bai et al, 2005;Chabot et al, 2005;Qu et al, 2007;Chen et al, 2008;Xia et al, 2008). In our experiment, the diurnal stem sap flux of Artemisia ordosica varied regularly and showed consistent patterns of day and night cycles with different stem diameters.…”
Section: Discussionsupporting
confidence: 49%
See 4 more Smart Citations
“…Sap flow measurements have been widely used to study plant response to environment factors (Cermak et al, 2004;Bai et al, 2005;Chabot et al, 2005;Qu et al, 2007;Chen et al, 2008;Xia et al, 2008). In our experiment, the diurnal stem sap flux of Artemisia ordosica varied regularly and showed consistent patterns of day and night cycles with different stem diameters.…”
Section: Discussionsupporting
confidence: 49%
“…In our study, sap flow rate had similar tendency with different diameters as shown in Figure 1; therefore, sapwood area could be used as a reasonable scalar for upscaling in Artemisia ordosica. During the entire experimental period, the mean trunk sap flux of Artemisia ordosica was 190Ð175 g/day, and decreased from May to October mainly due to the low temperature and photosynthesis (Qu et al, 2007). There was a significant linear relationship between sap velocity and the evapotranspiration rate ET 0 , with a correlation coefficient of R 2 D 0Ð6368 in the daily time scale.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations